Management accounting for the hospitality, tourism, and leisure industries: A strategic approach - Atkinson, Anthony A.; Kaplan, Robert S.; Young, Mark S. (Singapore, 2006)
The goal is the same: creating value. One company may be improving workforce conditions while another may be investing in new product development based on customer feedback. Whatever the strategy, the only management accounting textbook that understands and teaches how to use measurement and management systems for value creation is Management Accounting, Fourth Edition.
Keywords: Management Accounting